Pembelajaran Adaptif dalam Matematika SMP: Sebuah Kajian Literatur tentang Pemanfaatan Teknologi - Ema Dharmawati (International Forum of Researchers and Lecturers, 2023)
Education plays a central role in community development and the enhancement of human resources. In the rapidly evolving digital era, information and communication technology has significantly transformed the education landscape. Technology has become an integral part of the teaching and learning process in schools, bringing both challenges and significant opportunities. Particularly at the Junior High School (SMP) level, subjects like Mathematics, Natural Sciences (IPA), Physics, and Chemistry play a central role in shaping students' foundational knowledge. However, students often have varying levels of understanding and different learning styles. This poses a challenge for teachers trying to meet the diverse learning needs of their students. The use of the same linear teaching methods for all students is often ineffective in such a context. In this research, we employed a literature review methodology. This approach helps summarize and synthesize existing knowledge on the role of technology in enhancing student motivation in Science, Technology, Engineering, and Mathematics (STEM) education. By analyzing trends, findings, and patterns emerging from related literature, we can establish a strong knowledge base for this research. The adaptive learning approach, leveraging technology, has emerged as an intriguing solution. This approach allows for real-time analysis of student learning data and the adjustment of content, material, or teaching methods to suit individual needs. The research highlights the primary benefits of adaptive learning, such as personalized content adjustment, enhanced student motivation, more efficient monitoring and evaluation, and time savings in achieving better understanding. However, the research also acknowledges several challenges, including uneven technology infrastructure, the need for teacher training, and student data protection. Nevertheless, this research emphasizes the importance of adaptive learning in the context of STEM education at the SMP level in the digital era, while recognizing the need for further research to explore the potential of technology in enhancing the quality of education at this level.